The Effect of Capital Intensity, Company Size, Independent Commissioners, Financial Distress on Tax Avoidance - Fitria Eka Ningsih; Hari Stiawan (EAJ (Economic and Accounting Journal), 2025)
This research aims to analyze the effect of capital intensity, company size, independent commissioners, and financial distress on tax avoidance. The study uses secondary data sourced from the financial statements of food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the period 2018–2022. A total of 23 companies were selected through purposive sampling. The study investigates four independent variables: Capital Intensity (X1), Company Size (X2), Independent Commissioners (X3), and Financial Distress (X4), with Tax Avoidance (Y) as the dependent variable. The panel data regression analysis is applied as the research method, and data processing through EViews 12 identifies the Fixed Effect Model (FEM) as the most appropriate. The results indicate that, individually, Capital Intensity, Company Size, Independent Commissioners, and Financial Distress significantly influence Tax Avoidance. Additionally, these variables collectively have a combined impact on Tax Avoidance.